Pengaruh Pengetahuan Investasi, Persepsi Risiko, Dan Modal Investasi Terhadap Minat Berinvestasi Di Pasar Modal Pada Para Calon Investor Di Kota Gresik - Saputra, Hardiansyah (PRAGMATIS, 2024)
The research study is intended to test the impact of investment knowledge, risk perception and investment capital on interest in investing in the capital market for potential investors in Gresik City. As a contrast, the research also aims to examine the impact of investment knowledge, risk perception and investment capital on interest in investing in the capital market among potential investors in Gresik City. Quantitative research was applied for this research study, the respondents used were 90 people who involved the community in Menganti District, Gresik Regency. Purposive sampling is a way of taking samples with predetermined criteria. The questionnaire is a tool for collecting data which is then analyzed using Multiple Linear Regression assisted by the SPSS program. This test shows that the investment knowledge and risk perception variables do not have a significant impact on investment interest in the capital market for potential investors in Gresik City. On the other hand, the investment capital variable has a significant impact on interest in investing in the capital market for potential investors in the city.